2006
DOI: 10.1038/sj.gene.6364361
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide linkage analysis of 160 North American families with celiac disease

Abstract: Celiac disease (CD) is a common autoimmune disease caused by exposure to the protein gliadin in wheat, and related prolamins in barley and rye. The prevalence of the disease in the US is 1:133. The aim of this study was to identify non-human leukocyte antigen (HLA) loci that predispose to CD. A genome-wide search of 405 microsatellite markers was performed on DNA samples from 160 families with a minimum of two cases of CD. Multipoint, parametric and non-parametric linkage (NPL) analyses were performed. Locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…8 The PPP6C and PBX3 loci are located in 9q. This region showed linkage to CD in the North American population 9 but, in contrast to 2q33, no replication has been reported. Further studies are necessary to confirm this possible linkage region and, if replicated, to look for the etiologic genes.…”
Section: Resultsmentioning
confidence: 72%
“…8 The PPP6C and PBX3 loci are located in 9q. This region showed linkage to CD in the North American population 9 but, in contrast to 2q33, no replication has been reported. Further studies are necessary to confirm this possible linkage region and, if replicated, to look for the etiologic genes.…”
Section: Resultsmentioning
confidence: 72%
“…Probands were CD patients with a reported family history of CD from the Pediatric Gastroenterology Clinic of the Soroka University Medical Center, Israel, the only hospital in the Negev region. Families were ascertained through sequential sampling of first-degree relatives of CD cases, with diagnostic criteria as described in Garner et al 14 The results of the multipoint linkage analysis are shown in Figure 1 Multipoint linkage results for autosomal chromosomes. Genotypes from a 10-cM density microsatellite marker genome scan of 405 short-tandem repeat (STR) markers were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…There have been multiple genome-wide linkage studies to identify loci for CD (reviewed in van Heel et al, 13 Garner et al, 14 Eller et al…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their inherent features, tandem repeats have been widely used in genetic fingerprinting and as the genetic markers in linkage studies to locate the chromosomal regions harboring the mutations or genes for monogenic or familial disorders, complex diseases and quantitative traits. [41][42][43][44] Although tandem repeats are more informative than SNPs at the individual marker level, their number is far less than the several million SNPs in the human genome. Thus, tandem repeats are not ideal genetic markers for applications that require high marker density or resolution, such as genome-wide association studies (GWASs), in which several hundred thousand of SNPs are needed.…”
Section: The Evolution Of Genetic Markers In Disease Gene Mappingmentioning
confidence: 99%
“…However, microsatellites were widely used as the genetic markers in linkage studies. [41][42][43][44] These genetic variations have been used as the markers in human genetic studies for more than 20 years until the completion of the Human Genome Project 50 and the finding of millions of SNPs by the International SNP Map Working Group and other studies. 5,6 Thereafter, SNPs became the primary markers in genetic association studies, and also replaced microsatellites in some linkage studies.…”
Section: The Evolution Of Genetic Markers In Disease Gene Mappingmentioning
confidence: 99%